A rare outcome of myocardial infarction by the development of peri-infarction pericarditis: a case report - Park, Jungwoo; Serajian, Asif (International Journal of Research in Medical Sciences, 2024)
Peri-infarction pericarditis is a rare complication of myocardial infarction (MI), which can mimic the symptoms of recurrent infarction. In this report, we present the case of a 52-year-old male admitted to the emergency department (ED) with the symptoms of chest pain and hypertension. The patient presented with 10 hours of worsening chest pain. Upon admission to ED, his blood pressure was uncontrolled (165/105). The patient had a normal physical examination. Chest X-ray and computed tomographic angiography (CTA) results were non-significant. An electrocardiogram (ECG) showed sinus rhythm and ST elevation in lead II, III, and aVF, indicating acute inferior wall ST-elevation MI (STEMI). An emergency coronary angiogram procedure was performed and the patient was found to have 95% stenosis of the mid portion of the right coronary artery with a thrombus. An intracoronary stent was placed at the location without complications. Subsequently, the patient continued to report 10/10 chest pain. Another emergency coronary angiography procedure was performed and a patent right coronary artery stent was noted. At 36 hours after the procedure, the patient continued to have symptoms, therefore another ECG was performed. A new anterior injury pattern was noted, suggesting acute MI/STEMI and the patient was taken to a third coronary angiography procedure. No new findings were noted with widely patent stent and no evidence for distal embolization. After reviewing all findings, a diagnosis of post-MI pericarditis was made. The patient was started on colchicine and was discharged the following day. On subsequent follow-up, his symptoms improved.